Mutual Fund Performance Persistence and Competition: Pakistan’s Open Ended Mutual Fund Performance Analysis - Yasir Khan; Dr. Saima Batool; Mukharif Shah; Mukharif Shah (Journal of Business & Tourism, 2021)
Mutual Funds through its professional managers enable small investors to enjoy benefits of capital market with small amount. This study with special focus on Pakistani Mutual Fund industry, tests the suitability of traditional measures and multifactor, asset pricing models on the Mutual Fund performance. Owing to rareness of the applicability of the multifactor models in comparison to traditional measures, in evaluating Mutual Fund performance in modern day Pakistani research, the study uses CAPM, Fama French, Carhart models in the performance evaluation of Pakistan Mutual Fund. The data of 100 open-end Mutual Funds, for the period 2005 to 2017 was collected from Mutual Fund Association of Pakistan; while the risk free rates data was collected from State Bank of Pakistan and Stock data from Pakistan Stock Exchange for predicting the results, Ratio analysis, CAPM, Fama French-3 Factor and Carhart-4 factor model were used to understand its suitability. The results demonstrated that application of CAPM, affect market factors of majority of the portfolios.Where as in other two models (Fama French, Carhart) the majority of the portfolios are insignificantly affected by the size factor, value factor and Momentum factor. The Gibbon Rose Shanken unveils the suitability of the best model and justify CAPM as the better model among the three competing models in evaluate on theMutual Fund performance in Pakistan. The study has certain implications for the managers of assets management companies as well as useful for the investors in knowing which funds perform better and which kind of funds are ideal for investment.